Cannibal - Sinclair, Safiya (Lincoln : University of Nebraska Press, 2016)
"Colliding with and confrontingThe Tempest and postcolonial identity, the poems in Safiya Sinclair's Cannibal explore Jamaican childhood and history, race relations in America, womanhood, otherness, and exile. She evokes a home no longer accessible and a body at times uninhabitable, often mirrored by a hybrid Eve/Caliban figure. Blooming with intense lyricism and fertile imagery, these full-blooded poems are elegant, mythic, and intricately woven. Here the female body is a dark landscape; the female body is cannibal. Sinclair shocks and delights her readers with her willingness to disorient and provoke, creating a multitextured collage of beautiful and explosive poems"--
"Framed by "The Tempest" and calling on historical, cultural, and biological sources, "Cannibal" is a provocative poetic exploration of the female body, identity, and race"--
I. Home ; Pocomania ; In childhood, certain skies refined my seeing ; Fisherman's daughter ; Hands ; Portrait of Eve as the anaconda ; Mermaid ; Catacombs ; Dreaming in foreign ; Family portrait ; I shall account myself a happy creaturess ; Autobiography ; Osteology ; After the last austronauts had left us, I -- II. Notes on the state of Virginia, I ; America the beautiful ; Another white Christmas in Virginia ; One hundred amazing facts about the Negro, with complete proof, I ; One hundred amazing facts about the Negro, with complete proof, II ; One hundred amazing facts about the Negro, with complete proof, III ; Notes on the state of Virginia, II ; White apocrypha ; Notes on the state of Virginia, III ; Notes on the state of Virginia, IV ; Elocution lessons with Ms. Silverstone ; Litany for Charlottesville ; Notes on the state of Virginia, V -- III. Prayer book for vanishing ; Confessor ; Omen ; Good hair ; Woman, wound ; Woman, 26, remains optimistic as body turns to stone ; How to be an interesting woman: a polite guide for the poetess ; Birthmark, or purifying at the sink ; Little red plum ; Center of the world -- IV. After the last astronauts had left us, II (Laika) ; Spectre ; Chimera ; How to excise a tumor ; Incorrigible ; August ghost ; A separation ; In the event of the last unhappiness, return to the sea ; August in the country of another ; Kingdom-come ; The art of unselfing ; Doubt -- V. Crania Americana ; Notes.
NLJCols20082021
Keywords: Women -- Identity -- Poetry; Human body -- Poetry; POETRY -- American -- General; POETRY -- Caribbean & Latin American; Human body; Women -- Identity; Jamaican poetry -- Women authors; American poetry -- African American authors; Poetry; Poetry